RI 4231 Yancey-Crawford Manganese Deposit Rockingham County, Va. - M. H. Kline; Wing G. Agnew (The National Institute for Occupational Safety and Health (NIOSH), 1948)
"INTRODUCTION The Yancey-Crawford tract, located 1-1/2 nines east of Yancey station on the Norfolk & Western Railway in Rockingham County, Va. was from 1917 to 1941 considered an unusually promising manganese prospect. Because of the favorable geologic formations and because of the common occurrence of manganese in the district and Virginia's large production of these minerals from this area, geological report 3/ have listed this tract as the No. 1 prospect in the State. During World War I, extensive geologic studies were made to locate manganese deposits similar to those exploited at the Crimera mine near Waynesboro to alleviate this mineral shortage during the existing emergency.In September 1941 the Bureau of Mines started exploratory drilling on the tract in an effort to discover and block out reserves of manganese minerals as authorized by the 76th Congress under the Strategic Materials Act. After five drill holes wore sunk, the project was terminated October 1941."